Dissolved organic phosphorus utilization by phytoplankton reveals preferential degradation of polyphosphates over phosphomonoesters ... - Diaz, Julia M.; Holland, Alisia; Sanders, James G.; Bulski, Karrie; Mollett, Douglas; Chou, Chau-Wen; Phillips, Dennis; Tang, Yuanzhi; Duhamel, Solange (Columbia University, 2018)
The nutritionally available pool of dissolved organic phosphorus (DOP) supports marine primary productivity in a range of ocean ecosystems but remains poorly resolved. Here, the relative lability of model phosphorus (P) compounds representing the major P(V) bond classes of marine DOP – phosphomonoesters (P-O-C) and phosphoanhydrides (P-O-P) – was assessed in diatom cultures of the genus Thalassiosira, as well as coastal field sites of the western North Atlantic. In diatom samples, maximum enzymatic hydrolysis rates revealed that the P-anhydride bonds of inorganic tripolyphosphate (3poly-P), followed by the P-anhydride bonds of adenosine 5′-triphosphate (ATP), were preferentially degraded relative to the P-monoesters adenosine 5′-monophosphate (AMP) and 4-methylumbelliferone phosphate (MUF-P). Consistent with these rate measurements, targeted proteomics analysis demonstrated that the underlying phosphatase diversity present in diatom samples was dominated by P-anhydride degrading enzymes (inorganic ...